FREQUENCY OF LUNG CANCER DIAGNOSED BRONCHOSCOPICALLY IN A TERTIARY CARE CHEST FACILITY - Khan, Mir Azam; Adnan, Muhammad Atta ur Rehman; Khattak, Afaq; Ahmad, Fahad; Sajid, Hassan; Jadoon, Mohsin Khan; Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate various types of lung malignancies diagnosed through bronchoscopy, and their Methodology: This descriptive study was based in a tertiary care chest facility in Peshawar. Duration of the study was from June 2005 - June 2009. The material was obtained from the bronchoscopy record in the chest clinic. All the patients bronchoscoped from June 2005 – June 2009 were studied for their outcome. Result: This study included 425 patients, 306 (72%) were males and 235 (55.3%) of patients were between 31-60 years age. Ninety two (21.6%) patients were diagnosed with lung cancer; of which 73 (79.5%) patients were males and 19 (20.5%) were females. Sixty five (70.7%) of the 92 patients initially presented with shadow on the Chest radiograph, 9 (9.80%) patients had superior vena caval obstruction, 8 (8.70%) patients presented with lung collapse, 6 (6.52%) with haemoptysis, and 4 (4.35%) patients with hoarseness of voice. Forty three (46.7%) patients were diagnosed with squamous cell carcinoma, 29 (31.5%) with adenocarcinoma, 17 (18.5%) with small cell type carcinoma and 3 (3.30%) patients had large cell type carcinoma. Fifty four (58.7%) patients of the 92 were smokers or had a history of smoking, Anthracosis was found in 45 (10.6%) patients out of all the 425 patients. Conclusion: Commonest type of lung cancer in this study was squamous cell (46.7%) followed by adenocarcinoma (31.5%) and small cell carcinoma (18.5%). Squamous cell carcinoma was strongly associated with cigerrete smoking as compared to adenocarcinoma in this study. presentations.